2017
DOI: 10.21860/medflum2017_182955
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in women

Abstract: Sažetak. Urinarna inkontinencija definira se kao nevoljno otjecanje mokraće i predstavlja zdravstveni, higijenski i socijalni problem. Raspon tegoba je raznolik, od vrlo oskudnog i povremenog nevoljnog gubitka mokraće do potpune nemogućnosti kontrole mikcije. Stresna inkontinencija uz urgentnu te mješovitu najčešći su tipovi urinarne inkontinencije u žena. U članku su prikazane osnove dijagnostike i liječenja urinarne inkontinencije u žena. Urinarna inkontinencija predstavlja značajan zdravstveni problem brojn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Reversible incontinence is a transient type of incontinence (for example incontinence in pregnancy). Irreversible or permanent incontinence is a type of incontinence in which there is no possibility of recovery, and the intent is to prevent infections and focus on quality of life (4). Research has shown that UI affects millions of adults around the world (3).…”
Section: Introductionmentioning
confidence: 99%
“…Reversible incontinence is a transient type of incontinence (for example incontinence in pregnancy). Irreversible or permanent incontinence is a type of incontinence in which there is no possibility of recovery, and the intent is to prevent infections and focus on quality of life (4). Research has shown that UI affects millions of adults around the world (3).…”
Section: Introductionmentioning
confidence: 99%